Peranan Penyuluh Pertanian Lapangan (PPL) sebagai Fasilitator dalam Penggunaan Metode Belajar Pendidikan Orang Dewasa (Andragogi) (Kasus di Gapoktan Madani, Desa Sampalan Klod, Kecamatan Dawan, Kabupaten Klungkung, Provinsi Bali) - WIBOWO, HADI SURYO; SUTJIPTA, NYOMAN; WINDIA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
The Role of Agricultural Field Extensionist (PPL) as a Facilitator in Using Adult Learning Method (Andragogy), (Case in Gapoktan Madani, Sampalan Klod Village, Dawan Sub-district, Klungkung Regency, Bali Province) Agricultural extension acts as an agent for the change of farmers, which is by encouraging farmers to change their perceptions and behaviors to become farmers with better ability and able to make their own decisions, which in turn will gain a better life.The importance of the extensionist role and the importance of an innovation conveyed by him, the extension agent should be able to become a facilitator who can foster and improve the ability of farmers in an effort to change lives for the better. This study aims to identify the role of the extension facilitators in using adult education methods (andragogy). This research was conducted in a combination of farmer group (Gapoktan) Madani, Sampalan Klod Village, Dawan Sub-district, Klungkung Regency, Bali Province. The location of this study was chosen purposively or deliberately based on several considerations. The respondent collected using census method in accordance with the number of active members of the farmer group as many as 60 people. This research uses the descriptive qualitative analysis method, which aims to give description and explanation about variables studied. Based on the results of the research, it is known that the role of agricultural field extension as a facilitator in the use of adult education learning method (andragogy) is included in the good category with the achievement score of 4.11. This means that the extension officer in Gapoktan Madani has been able to perform his role well as a facilitator in the use of adult education learning method (andragogy).